I wish that I had duck feet - Seuss (London HarperCollins Children's Books, 2004)
What would life be like if you had feet like a duck, or horns like a deer, a whale spout on your head, or a long, long nose? In this crazy tale a small boy imagines all these things, only to decide in the end that perhaps it$1 (Bs better to be (3z(BME(3y (Bafter all.s